Legal Regulation of the Rights of Orphaned Children in the Kurdistan Region of Iraq - أحمد, د. رِوبار مجيد (Sulaimani Journal for Humanities, 2025)
This research addresses the rights of children with autism in the Kurdistan Region, highlighting the suffering these children and their families endure due to the lack of specialized centers providing appropriate care and treatment. The research also emphasizes the need for legislation to protect their rights and provide necessary support for their families. It focuses on the importance of creating a suitable environment for children with autism, including the establishment of specialized government centers to ensure they receive the necessary care. Furthermore, it addresses the need to activate local and international laws that support the rights of these children and establish clear standards for their treatment. The research aims to raise awareness about the rights of children with autism in the Kurdistan Region and to stress the necessity of collective action to improve their situation, whether through the provision of healthcare or psychological and social support. It also seeks to convey a message to relevant authorities about the need to develop effective strategies to improve the lives of these children and their families. Finally, this research aims to offer recommendations to improve laws and policies related to the rights of children with autism, ensuring they enjoy a dignified life like other children.